Neurotechnology and neural rights - Andrijauskaitė, Ieva (Vilnius University Open Series, 2025)
Neurotechnology, which includes a range of devices and procedures that interact directly with the human nervous system, has become a pioneering field with the potential to revolutionize medicine, communication and human development. The rapid progress and constant development poses complex serious ethical and legal challenges. Especially, with regard to human rights such as mental privacy and cognitive freedom. The paper explores the definition and examples of neurotechnologies and its applications, their impact on cognitive behavior and emotions, the human rights they affect, and the emerging concept of neural rights. Existing systems are analyzed through a legal lens and the need to balance between innovation and ethical imperatives is sought.